Great gerbil burrowing-induced microbial diversity shapes the rhizosphere soil microenvironments of Haloxylon ammodendron in temperate deserts - Dang, Hanli; Zhao, Wenqin; Zhang, Tao; Cheng, Yongxiang; Dong, Jianrui; Zhuang, Li (Frontiers in Microbiology, 2022)
In the Gurbantunggut Desert of northwest China, the main habitat of Rhombomys opimus (great gerbil) is under the thickets of Haloxylon ammodendron, the main construction species. In the long-term coexistence, continuous gerbil activities (burrowing, defecating and gnawing) limited the growth of H. ammodendron, affected the root microenvironment under the H. ammodendron forest, and weakened the desert ecosystem. However, there is a lack of general understanding about the response of desert soil microhabitats to such gerbil disturbance. Accordingly, this study examined the effects of different intensities of gerbil disturbance (none, mild, moderate, or severe disturbances) on soil nutrients content and used high-throughput sequencing to explore the change in diversity and structure of microbial communities (bacteria and fungi) in H. ammodendron rhizosphere at different soil depths (0-20, 20-40, and 40-60 cm). In the arid desert ecosystem, compared with the soil fungal community, the alpha diversity of the soil bacterial community was significantly affected by gerbil disturbance. Meanwhile, both soil depth and gerbil disturbance significantly impacted the beta diversity and relative abundance of soil bacterial and fungal communities. In addition, gerbil disturbance significantly altered the soil characteristics affecting the distribution and composition of soil microbial communities in H. ammodendron rhizosphere, especially the soil bacterial community. This survey provides evidence that remold impact of gerbil disturbance on soil microenvironment of H. ammodendron rhizosphere in desert ecosystems in northwest China, which helpshelp to further understand the potential correlations with changes in the microbial community at a regional scale.